1993
DOI: 10.7589/0090-3558-29.2.237
|View full text |Cite
|
Sign up to set email alerts
|

The Epizootiology of Eustrongylidosis in Wading Birds (Ciconiiformes) in Florida

Abstract: A total of 2,167 individuals representing 15 species of wading birds was examined for infection with the nematode Eustrongylides ignotus in Florida (USA). Ten of the species were infected with the greatest prevalences occurring in great blue herons (Ardea herodius) (33%), great egrets (Casmerodius albus) (22%), and snowy egrets (Egretta thula) (19%). Among nestlings, prevalences increased with age. This parasite was estimated to cause at least 80% mortality among nestling ciconiiforms at one colony in Everglad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 10 publications
2
25
0
1
Order By: Relevance
“…Our specimens were in poor condition and could not be identified to the species level, but a search of the literature failed to reveal a report of this nematode in pelicans. These worms cause epizootics in nesting wading birds (Spalding et al, 1993). Immature forms of Eustrongylides ignotus (JĂ€gerskiöld, 1909) were reported as a new Caribbean record in Puerto Rican fishes by BunkleyWilliams & Williams (1994).…”
Section: Resultsmentioning
confidence: 99%
“…Our specimens were in poor condition and could not be identified to the species level, but a search of the literature failed to reveal a report of this nematode in pelicans. These worms cause epizootics in nesting wading birds (Spalding et al, 1993). Immature forms of Eustrongylides ignotus (JĂ€gerskiöld, 1909) were reported as a new Caribbean record in Puerto Rican fishes by BunkleyWilliams & Williams (1994).…”
Section: Resultsmentioning
confidence: 99%
“…The 122 ha area converted to open water is about 100 cm deep, and so the amount of carbon released from the marsh is about 450 thousand mt C year -1 . There are other issues, including that the un-managed distribution of pathogens into a nutrient-and organicrich system is a fertile growth medium for organisms potentially compromising the health of people and avians (Anza et al 2014;Coyner et al 2003;Spalding et al 1993;Petrie et al 2016), and that contaminates local streams-a subject that can be explored in more detail elsewhere. The consequences potentially apply to other marshes with significant vertical water movements and eutrophic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In Florida (USA) the number of reproducing wading birds (Ciconiiformes) has declined dramatically over the past 40 yr (Ogden, 1994). Spalding et al (1993) reported that infection with the parasitic nematode Eustrongylides ignotus was a major mortality factor in nestling wading birds in Florida, causing losses of over 80% in some colonies. Birds become infected with this parasite after consuming fish.…”
Section: Introductionmentioning
confidence: 99%